Extraction and Characterisation of African Star Apple (Chrysophyllum albidum) Seed Oil and the Adsorptive Properties of the Fruit Shell in Ghana - Michael A. Anang; Michael Oteng-Peprah; Kwasi Opoku-Boadu (International Journal of Food Science)
This research work was undertaken to determine the physicochemical parameters of oil from the seeds of African Star Apple (Chrysophyllum albidum) and further evaluate the adsorptive properties of the fruit shell. The oil was extracted using hexane with the soxhlet apparatus at a temperature of 65°C for 4 hours. The results showed an average oil yield obtained of 11.6%, specific gravity of 0.92kg/m3, the refractive index of 1.464 at 30°C, an acid value of 7.72 mg KOH/g, a free fatty acid value of 3.16 g/100g, saponification value of 200.56 mg KOH/g, and an iodine value of 70.64 g/100g. A Fourier Transform Infrared (FTIR) study on the oil identified some triglycerides, carbonyl, alkane, and alkene compounds. Adsorptive studies of the fruit shell for the removal of dye were also performed after chemical activation with CaCl2, MgCl2, and ZnCl2. The kinetics of the adsorption favoured a pseudo-first-order reaction pathway for CaCl2 with R2 of 0.941 while ZnCl2 and MgCl2 favoured a pseudo-second-order reaction pathway with R2 of 0.914 and 0.973, respectively.